Contesting Cosmopolitan Europe : Euroscepticism, Crisis and Borders - James Foley; Umut Korkut (Routledge, 2025)
The project of European integration has undergone a succession of shocks, beginning with the Eurozone crisis, followed by reactions to the sudden growth of irregular migration, and, most recently, the coronavirus pandemic. These shocks have politicised questions related to the governance of borders and markets that for decades had been beyond the realm of contestation. For some time, these questions have been spilling over into domestic and European electoral politics, with the rise of “populist” and Eurosceptic parties. Increasingly, however, the crises have begun to reshape the liberal narratives that have been central to the European project. This book charts the rise of contestation over the meaning of “Europe”, particularly in light of the coronavirus crisis and Brexit. Drawing together cutting edge, interdisciplinary scholarship from across the continent, it questions not merely the traditional conflict between European and nationalist politics, but the impact of contestation on the assumed “cosmopolitan” values of Europe.